A qualitative research study to provide an in-depth understanding of Millennials and their perspectives on motivational factors used within the retail industry - Smith, Gareth (The IIE, 2018)
Millennials have been identified to be the workers that will make up 35% of the global workforce by 2020 (Leng & Wong, 2017). This research report aimed to describe Millennials, the newest generation of workers to enter the workplace. Currently, organisations have been identified to be making changes to existing frameworks and policies to accommodate for these “Millennials”. However, despite these changes, Millennials have been regularly identified to be leaving the organisation for another. Whilst attempting to understand Millennials. This study together with the use of Herzberg’s motivation theory, aimed to generate an in-depth understanding of the Millennials using an interpretivist, qualitative approach. In particular, the study reviewed the motivation factors of a particular organisation to identify if this was a particular area as to why Millennials are leaving. For the collection of data, a semi-structured interview was used whilst Braun & Clark’s six step process of thematic analysis was used to analyse the data generated. The findings revealed that if managers don’t provide the various identified factors that Millennials require, these can be potential areas as to why Millennials will possibly leave. It was also noted that other areas need to researched to fully understand why Millennials are leaving.
Keywords: policies and frameworks; organisations; motivation factors; perspectives of millennials; millennials in the retail industry